The Leucine-Rich Repeat Receptor-Like Kinase BRASSINOSTEROID INSENSITIVE1-ASSOCIATED KINASE1 and the Cytochrome P450 PHYTOALEXIN DEFICIENT3 Contribute to Innate Immunity to Aphids in Arabidopsis. Issue 4 (28th February 2014) - Prince, David C.; Drurey, Claire; Zipfel, Cyril; Hogenhout, Saskia A.
Abstract : Aphid-derived protein elicitors trigger distinct plant innate immune responses that are dependent on BAK1 and PAD3 . Abstract: The importance of pathogen-associated molecular pattern-triggered immunity (PTI ) against microbial pathogens has been recently demonstrated. However, it is currently unclear if this layer of immunity mediated by surface-localized pattern recognition receptors (PRR s) also plays a role in basal resistance to insects, such as aphids. Here, we show that PTI is an important component of plant innate immunity to insects. Extract of the green peach aphid (GPA ; Myzus persicae ) triggers responses characteristic of PTI in Arabidopsis ( Arabidopsis thaliana ). Two separate eliciting GPA -derived fractions trigger induced resistance to GPA that is dependent on the leucine-rich repeat receptor-like kinase BRASSINOSTEROID INSENSITIVE1-ASSOCIATED KINASE1 (BAK1)/SOMATIC-EMBRYOGENESIS RECEPTOR-LIKE KINASE3, which is a key regulator of several leucine-rich repeat-containing PRR s. BAK1 is required for GPA elicitor-mediated induction of reactive oxygen species and callose deposition. Arabidopsis bak1 mutant plants are also compromised in immunity to the pea aphid ( Acyrthosiphon pisum ), for which Arabidopsis is normally a nonhost. Aphid-derived elicitors induce expression of PHYTOALEXIN DEFICIENT3 (PAD3), a key cytochrome P450 involved in the biosynthesis of camalexin, which is a major Arabidopsis phytoalexin that is toxic to GPA . PAD3 is also required for induced resistance to GPA, independently of BAK1 and reactive oxygen species production. Our results reveal that plant innate immunity to insects may involve early perception of elicitors by cell surface-localized PRR s, leading to subsequent downstream immune signaling.